The Business Case for Investment in Rangeland Restoration - Davies, Jonathan; Nyamtseren, Mandakh; Wane, Abdrahmane; Hientz, Lennart (Economics of Land Degradation Secretariat, 2025)
Rangelands occupy 54 % of the global terrestrial surface and they are used by around 500 million pastoralists.